The association of four-limb blood pressure differences with cardiovascular risk factors and target organ changes in elderly Chinese: The Northern Shanghai Study. (2nd April 2020) - Yu, Shikai; Lu, Yuyan; Xiong, Jing; Bai, Bin; Teliewubai, Jiadela; Chi, Chen; Blacher, Jacques; Li, Jue; Zhang, Yi; Xu, Yawei
ABSTRACT: Background : The association of four-limb systolic blood pressure differences (SBPDs) including inter-arm (IASBPD), inter-leg (ILSBPD) and ankle-brachial index (ABI) with cardiovascular risk factors and target organ changes (TOCs) remains controversial. This study aims at investigating the association of those parameters with cardiovascular risk factors and TOCs in an elderly Chinese population. Methods : A total of 1528 subjects derived from the Northern Shanghai Study were studied. Four-limb BPs were simultaneously measured by VP-1000 device. Cardiovascular risk factors and TOCs including parameters of left ventricular structure and function, carotid intima-media thickness, carotid-femoral pulse-wave velocity (CF-PWV), estimated glomerular filtration rate (eGFR) and urinary albumin/creatinine ratio, were evaluated with standardized methods. Results : ABI significantly associated age (β = −0.004, p < .01), female gender (β = 0.02, p < .01), body mass index (β = −0.004, p < .01), smoking (β = −0.04, p < .01), high-density lipoprotein (β = 0.04, p < .01), low-density lipoprotein (β = −0.01, p = .01) and diabetes mellitus (β = −0.02, p < .01), while the fourth root of IASBPD significantly associated with body mass index (β = 0.03, p < .01), high-density lipoprotein (β = −0.10, p = .02) and brachial SBP (β = 0.003, p < .01); the fourth root of ILSBPD significantly associated with high-density lipoprotein (β = −0.12, p < .01) and diabetes mellitus (β = 0.09, p = .01). IASBPD, ILSBPD, and ABI all significantly associated with CF-PWV and eGFR (all p < .05) in either unadjusted or adjusted models, but not with other TOCs. Conclusion : Four-limb SBPDs, namely ABI, IASBPD, and ILSBPD, bore various burdens of cardiovascular risk factors and significantly and independently associated with CF-PWV and eGFR.